SPECIAL NEEDS STUDENTS, WHAT ARE THE CHALLENGES? - Irsyad Nugraha; Raynesa Noor Emiliasari; Muhammad Soni; Bayu Ali Wardana (Institut Pendidikan Indonesia Garut, 2023)
Special education seems to have to be considered one of the most stressful jobs in the education sector. Experts must convey highly specialized teaching methods that support a variety of different learning environments, alignment social and emotional development with firm academic achievement, and finally equip their pupils for a world that impose many real difficulties, and any method of instruction has obviously been a truly massive challenge. Thereby, the objective of this research was to reveal the challenges that English teachers confront while teaching Special Needs Students. The subjects of this research included an English teacher from such a special needs school who had significant experience teaching English. A semi-structured interview was employed to collect data. In accordance with the findings, the most daunting problem that teachers face when teaching English is listening skills. Further to that, the teacher is knowledgeable about teaching concepts, techniques, and problem-solving strategies.